Short Communication: Identification of the exon 1 myostatin gene polymorphism and its association with slaughtered weight in Indonesian Kampung and Broiler Chicken - Linda Suhartati; ISYANA KHAERUNNISA; ASEP GUNAWAN; RUKMIASIH RUKMIASIH; SRI DARWATI; CECE SUMANTRI; RIZQAN RIZQAN (Society for Indonesian Biodiversity, 2020)
Abstract. Suhartati L, Khaerunnisa L, Gunawan A, Rukmiasih, Darwati S, Sumantri C, Rizqan. 2020. Short Communication: Identification of the exon 1 myostatin gene polymorphism and its association with slaughtered weight in Indonesian Kampung and Broiler Chicken. Biodiversitas 21: 3893-3897.  Myostatin is widely known as a negative regulator of skeletal muscle development by controlling hypertrophy and hyperplasia. Silent mutation in exon 1 (c.234G>A) was then thought to be associated with chicken growth performances. This study was designed to analyze polymorphisms of c.234G>A mutation of the myostatin gene and its effect on slaughtered weight in Indonesian Kampung and meat-type chicken. The SatI restriction enzyme was used for genotype determination through the PCR-RFLP technique. The effect of genotype on the slaughtered weight was analyzed using the General Linear Model (GLM) procedure. Genotyping was performed on 138 chicken from Kampung (n=67) and meat type (cobb Broiler) (n=71) chicken. The amplification product contained 226 bp nucleotides. This myostatin gene was polymorphic in both chicken population, produced 2 alleles (G and A), and 3 genotypes (GG, GA, and AA). The A allele had a higher frequency than the G allele in all populations. In this study, genotype of AA and GA had higher live weight, carcass weight, breast weight, thigh weight, drumsticks weight, wings weight, breast muscle weight, thighs muscle weight, drumsticks muscle weight than GG genotype of 12 weeks-old Kampung chicken. The results suggested that the c.234G>A mutation in exon 1 could be potentially recommended as a genetic marker for chicken slaughtered weight traits.